Hazardous work exposures and working conditions and the risk of serious injury among Latino day laborers in Houston, Texas (2014–2021) - Fernandez-Esquer, Maria Eugenia; Pinzon-Gomez, Cesar Leonardo; Monforton, Celeste; Li, Yuan; Maroufy, Vahed; Ojeda, Martha; Rodriguez, Anabel (Frontiers in Public Health, 2025)
IntroductionLatino day laborers (LDLs) are frequently exposed to workplace hazards that increase their risk of an injury. The purpose of this study was to assess the relative influence of worker and workplace characteristics on serious injuries reported by LDLs at four different time points. We examined the influence of demographic characteristics, hazardous chemical exposures and working conditions using data from four cross-sectional surveys conducted between 2014 and 2021.MethodsA total of 740 LDL were randomly recruited from public job hiring locations (known as “corners”) in Houston Texas to participate in surveys conducted as part of injury risk reduction studies. Spanish speaking interviewers followed a rigorously tested field methodology and administered a previously validated survey instrument. Data from four cross-sectional surveys were each examined separately and then jointly to determine the covariates associated with serious injuries.ResultsMultivariable logistic regression analysis revealed significant year-to-year variability in the associations between hazardous chemical exposures, working conditions, and reported serious injuries. Gasoline exposure emerged as the strongest predictor across survey years. Analysis of the aggregated data indicates that exposure to gasoline, to dust and gasses, and to working conditions that include the risk of getting cut, and lack of ventilation, increased the odds of reporting a serious injury. By contrast, exposure to glue and adhesives was associated with a decrease in the odds of a reported serious injury. Demographic characteristics were not associated with reported injury per survey year or when data was aggregated.ConclusionOur findings indicate that serious injury is associated with the characteristics of the workplace and not the worker, as workplace hazards were significantly associated with serious injury, while worker demographic characteristics were not. The variability in workplace hazards associated with serious injury per survey year was expected in light of the constant job rotation reported by workers. Aggregated data confirmed initial findings and also highlighted new hazards, including those associated with a decreased risk for injury. Hazards confronted by LDL need to be considered globally, as their influence may vary by job, context, circumstances, and over time. Future research should examine how different exposures interact to influence injury risk. This understanding may benefit safety training programs and guide their efforts to reduce LDL risk of injuries at work.